COVID-19 and sensorineural deafness: systemic review - Hussain, Tanvir; Ghaznain, Amna; Patil, Nash (International Journal Of Community Medicine And Public Health, 2022)
Coronavirus is a pandemic that hits the world when least expected, causing health chaos. A plethora of evidence from recent studies indicates that the novel coronavirus (COVID-19) disease has led to various health problems. For instance, a range of neurological symptoms may worsen in the event of a Coronavirus infection. The virus is linked to sudden sensorineural deafness also (used in this article) known as (SSNHL) sudden sensorineural hearing loss. Studies indicate that due to the vulnerability of the inner ear to viruses, SSNHL is believed to develop after severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) exposure, frequently leading to prolonged morbidity and deterioration of quality of life. This is because otologic symptoms relating to SSNL outlined in patients with coronavirus infection. However, no definitive link has been found between COVID-19 and SSNHL. This systematic assessment investigated the relationship between the prevalence of SSNHL and COVID-19 disease. Additionally, the review utilizes patients having coronavirus-related sudden sensorineural hearing loss from the ENT outpatient department; all the patients in this review are at least 18 years of age. Sensorineural deafness generally appeared within a couple of days and two months following the COVID-19 diagnosis, while some individuals experienced it prior to the detection of COVID-19. As previously stated, the purpose of this article is to conduct a systematic literature review to assess the potential link between COVID-19 infection and SSNHL. SARS-CoV-2 might impair cochlear function, according to existing evidence; however, the evidence is scarce. To assess the long-term impact of this virus on the inner ear, substantial cohort and potential investigations are required.